A Review of Recent Evidence from Meal-Based Diet Interventions and Clinical Biomarkers for Improvement of Glucose Regulation - Jeong, Yeseung; Lee, Eunbi; Park, Yoon Jung; Kim, Yangha; Kwon, Oran; Kim, Yuri (Preventive nutrition and food science, 2020)
In recent decades, the prevalence of diabetes has rapidly increased worldwide. Medical nutrition therapy has been identified as a major therapeutic support for diabetic patients, while preventive strategies in prediabetic or high-risk individuals have mainly focused on supplementation with bioactive compounds. Recently, meal-based interventions have been investigated as novel and safe long-term strategies for improving glucose regulation. However, evaluation of meal-based interventions is difficult since it requires analysis of sensitive markers. Biomarkers can also be used to identify individuals at risk for diabetes, which is important for disease prevention. In this review, we summarize current evidence from meal-based intervention studies conducted with the aim of improving glucose homeostasis in individuals at risk of diabetes using clinical biomarkers currently used to assess diabetic risk. Very low-calorie diets have significantly improved glucose regulation in obese adults and in adults with type 2 diabetes mellitus. In particular, changing the ratios of macronutrients through calorie restriction reduces fasting glucose level and hemoglobin A1c levels in patients with diabetes mellitus. However, this effect is limited in both obese and healthy adults. To date, multiple glucose-related markers have been identified as clinical biomarkers of diabetes. Additional clinical biomarkers include cholesterol levels, hematological markers, and inflammatory markers. Taken together, the evidence presented in this review may help for selection of clinical biomarkers for meal-based preventive approaches for non- or pre-diabetic individuals to prevent onset of diabetes.